2001
DOI: 10.1159/000055107
|View full text |Cite
|
Sign up to set email alerts
|

Mito-FLAG as Salvage Therapy for Relapsed and Refractory Acute Myeloid Leukemia

Abstract: Background: This study was performed to examine the feasibility and toxicity of the combination of mitoxantrone, fludarabine, cytarabine as bolus (B) or continuous infusion (CI) and granulocyte- colony stimulating factor (G-CSF) in patients with recurrent and refractory acute myeloid leukemia (AML). Patients and Methods: 29 patients with relapsed (n =17) or refractory (n =12) AML were treated with the Mito-FLAG protocol consisting of mitoxantrone (7 mg/m2, days 1/3/5), fludarabine (15mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Myelosuppression-associated complications were similar to other salvage regimens (6,18,20,21,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 63%
“…Myelosuppression-associated complications were similar to other salvage regimens (6,18,20,21,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 63%
“…A number of studies of FLAG along with mitoxantrone for treating patients of refractory or relapsed AML have been reported. The CR rates were 59 and 67%, respectively (7,8). …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported on FLAG with mitoxantrone for treating patients with refractory or relapsed AML. The CR rates were 59 and 67%, respectively (7,8). However, to date there have been no reports of this regimen for relapsed AML solely.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in 29 patients with relapsed refractory AML, 17 patients (59%) achieved a CR and the median overall survival was 6.8 months. 22 Patients who have failed to respond or have relapsed after multiple lines of chemotherapy have a dismal prognosis. Encouragingly, adding fludarabine to intermittent-sequential high-dose cytarabine plus mitoxantrone produced a CR in 5/16 (31%) heavily pretreated AML patients; patients had received at least two lines of intensive first-and second-line chemotherapy.…”
Section: Refractory/relapsed Amlmentioning
confidence: 99%